Konflik dalam Novel Amelia Karya Tere Liye dan Rancangan Pembelajaran di SMA - Fathimah Nurhalimah S; Edi Suyanto; Munaris Munaris (FKIP Universitas Lampung, 2018)
The objective of research was to describe the conflicts in the novel and its learning design in senior high school. Qualitative descriptive method was used in the research. The source of data taken from Amelia novel by author Tere Liye published in 2013. The data which analized in the research was in the form of sentences and quotations of texts which were related to the events in Amelia novel and its learning design in senior high school. The results of the research showed that there were 4 conflicts stated in the novel. Amelia novel can be used in learning design as an alternative learning material for students of senior high school grade XII in even semester on based competence 3.9 by analizing its content and novel language structure on based competence 4.9 designing a novel by paying attention on its contents and language structures.Tujuan penelitian ini untuk mendeskripsikan konflik dalam novel Amelia karya Tere Liye dan rancangan pembelajarannya di SMA. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Sumber data dalam penelitian ini adalah novel Amelia karya Tere Liye yang diterbitkan pada tahun 2013. Data yang dianalisis dalam penelitian ini berupa kalimat dan kutipan teks yang berkaitan dengan peristiwa dalam novel Amelia karya Tere Liye dan rancangan pembelajarannya di SMA. Hasil penelitian menunjukkan bahwa konflik yang terdapat dalam novel Amelia karya Tere Liye ada 4 konflik. Novel Amelia dapat dibuat rancangan pembelajarannya sebagai alternatif bahan pembelajaran untuk siswa SMA kelas XII semester genap dengan KD 3.9 menganalisis isi dan kebahasaan novel dan KD 4.9 merancang novel dengan memerhatikan isi dan kebahasaan.Kata kunci: konflik, novel, rancangan pembelajaran.